Video games, cognitive exercises, and the enhancement of cognitive abilities. (August 2015) - Anguera, Joaquin A; Gazzaley, Adam
Highlights: Cognitive training tools fall into two bins: video games and cognitive exercises. Factors such as fun, motivation, and adaptivity often differ across approaches. Expectancy and dose size can influence study effects during validation experiments. Hybrid tools leveraging the strengths of each approach may guide this field forward. Abstract : In this review we explore the emerging field of cognitive training via distinct types of interactive digital media: those designed primarily for entertainment ('video games') and those created for the purpose of cognitive enhancement ('cognitive exercises'). Here we consider how specific design factors associated with each tool (e.g., fun, motivation, adaptive mechanics) and the study itself (e.g., participant expectancy, dose effects) can influence cognitive enhancement effects. We finally describe how the development of hybrid interventions that capitalize on strengths of each type of interactive digital media are anticipated to emerge as this field matures.